Kajian Teoritis: Mendalami Pemahaman Kasus Korupsi pada PT. Asuransi Jiwasraya (PERSERO) dengan Pendekatan Teori Dasar Fraud - Nasirwan; Desnia, Debora; Putri, Naswa Aprillia; Wahyuni, Siti Sri (Ikatan Da'i Indonesia, 2024)
This journal discusses the analysis of corruption cases at PT. Asuransi Jiwasraya (Persero) using a basic fraud theory approach. Jiwasraya, as a well-known insurance company in Indonesia, faced a major scandal related to finance and management. This research delves deeper into the case with a focus on the impacts of fraud both financially and non-financially. In this analysis, the author explores the causes and consequences of corruption practices that occurred in Jiwasraya. The basic fraud theory approach is utilized to understand how fraud can occur and its impacts on the company and society. The findings of this research provide insights into preventive measures that insurance companies and regulators can take to avoid similar scandals in the future. Additionally, this research also raises questions about supervision and legal responsibilities related to this case.